Plant-Based: A Perspective on Nutritional and Technological Issues. Are We Ready for “Precision Processing”? - Menta, Roberto; Rosso, Ginevra; Canzoneri, Federico (Frontiers in Nutrition, 2022)
The rapid evolution of consumers’ preference despite being still rooted in taste, is rapidly combining with an exponential growth of environmental awareness. Both are forcing innovation into the food industry sector. Today it's common in the scientific literature to find an awareness of nutrition and sustainability, functionality and freshness, taste and pollution: the most relevant and recognized trends are evolving with unprecedent speed towards a new paradigm. The perfect storm of fast-growing population together with an exploding level of environmental pollution, is combining with the request for functional foods with more defined health properties and is strongly pushing the food sector to new defined innovation objectives to keep and develop the economic role of most loved brands around the world. The most debated conundrum is how to provide healthy food to all human being, without further affecting our Mother Earth. Innovation in food raw materials as well innovation in food processing seems to be the magic solution to provide twice with half that is, to double the food production combined with declining resources. One of the fastest growing segments in the food industry is the plant-based segment. The status of the available options in food processing applied to plant-based food will be discussed, with a special focus on novel physical processing technologies and atomic force microscopy as possible complementary weapons in science-based definition of a sustainable nutrition approach. A call for a new paradigm such as “precision processing” should be adopted to drive the evolution of the whole food system.